Reset of Inflammatory Priming of Joint Tissue and Reduction of the Severity of Arthritis Flares by Bromodomain Inhibition. Issue 4 (2nd February 2023) - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al.
Abstract : Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extraterminal motif (BET) proteins translate epigenetic changes into transcription. Here, we used a BET inhibitor (I‐BET151) to target inflammatory tissue priming and to reduce flare severity in a murine experimental arthritis model. Methods: BALB/c mice were treated by intraperitoneal injection or by local injection in the paw with I‐BET151, which blocks the interaction of BET proteins with acetylated histones. We assessed the effects of I‐BET151 on acute arthritis and/or inflammatory tissue priming in a model of repeated injections of monosodium urate crystals or zymosan into the mouse paw. I‐BET151 was given before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. We performed transcriptomic (RNA‐Seq), epigenomic (ATAC‐Seq), and functional (invasion, cytokine production, migration, senescence, metabolic flux) analyses of murine and human SFs treated with I‐BET151 in vitro or in vivo. Results: Systemic I‐BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I‐BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic, and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, making them promising therapeutic targets for prevention of arthritis flares in previously affected joints.